Parameterized simplification logic I: reasoning with implications and classes of closure operators - Cordero-Ortega, Pablo; Enciso-García-Oliveros, Manuel; Mora-Bonilla, Ángel; Vychodil, Vilem (Taylor & Francis, 2020)
In this paper, we present a general inference system for reasoning with if-then rules. They are defined using general lattice-theoretic notions and their semantics is defined using particular closure operators parameterized by systems of isotone Galois connections. In this general setting, we introduce a simplification logic, show its sound and complete axiomatization, and deal with related issues. The presented results can be seen as forming parameterized framework for dealing with if-then rules that allows to focus on particular dependencies obtained by choices of parameterizations.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/5399?template=romeo
Keywords: Subrutinas (Programas de ordenador); Lógica simbólica y matemática; Formal Concept Analysis (FCA); Lógica difusa; Deducción automática y métodos de clausura